2015
DOI: 10.1186/s40064-015-0891-0
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment levels of the serum biomarkers CEA, CYFRA 21–1, SCC and the soluble EGFR and its ligands EGF, TGF-alpha, HB-EGF in the prediction of outcome in erlotinib treated non-small-cell lung cancer patients

Abstract: The aim of this study has been to investigate the potential of serum biomarkers used in clinical practice (CEA, CYFRA 21–1, SCC) together with the serum epidermal growth factor receptor (EGFR) and its associated ligands (EGF, TGF-α, HB-EGF) as outcome predictors of non-small cell lung cancer (NSCLC) patients treated with the TKI erlotinib. The pretreatment levels of these markers were evaluated through immunoassays carried out in 58 patients. The progression-free survival (PFS) and overall survival (OS) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…In addition, the diagnostic performance of the combination panel of these three lncRNA (AUC, 0.942) was significantly higher than that of CEA [13,14].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the diagnostic performance of the combination panel of these three lncRNA (AUC, 0.942) was significantly higher than that of CEA [13,14].…”
Section: Discussionmentioning
confidence: 92%
“…The major cellular functions of cytokeratins are mechanical support, cytoarchitecture, cell migration, and signal modulation26. Among keratins, the KRT19 is the smallest member of the type I keratin family and is known as a tumor marker in several kinds of malignancies12131415161718. Regarding the function of KRT19 in cancers, the expression of KRT19 might contribute to the invasiveness of hepatocellular carcinoma (HCC)27.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of identifying novel partner receptor for TD mutant HER2, we found that cytokeratin 19 (KRT19) is bind to wild type HER2 in A549 lung cancer cell line. KRT19, which is a member of the keratin intermediate filament family of proteins, is well known to be generally overexpressed in various cancers121314151617, and its fragment known as CYFRA has been shown to be a tumor marker in some subsets of lung cancers1218. In this study, we determined the binding sites of KRT19 and HER2 and investigated the impact of KRT19 and HER2 interactions in signal transduction pathways to decode their possible roles in oncogenesis.…”
mentioning
confidence: 99%
“…Another study demonstrated that pretreatment higher CEA (>5 ng/mL) was significantly associated with a higher OS as compared to the normal levels in patients receiving erlotinib. 64 The reason maybe that lung adenocarcinoma patients with high serum CEA levels are more likely to harbor EGFR-sensitive mutations 65,66 according to the study conducted in an unselected NSCLC population and a majority were lung adenocarcinoma patients. 64 A similar conclusion was obtained in another study; however, the cutoff value for CEA levels was 20 ng/ mL.…”
Section: Carcinoembryonic Antigenmentioning
confidence: 99%